Investigation of the temperature of electrons in a glow discharge plasma at direct current Ar and Ar/ C2H2 - Utegenov А.У.; Onaibergenov Ж.Е.; Abdrakhmanov A.Е.; Orazbaev С.А.; Ramazanov Т.С. (Recent Contributions to Physics, 2024)
This paper presents the results of the study of the electron temperature in argon and argon-acetylene plasma of DC glow discharge. The optical-emission method was used to determine the main parameter of the complex plasma. The dependence of the electron temperature on the operating pressure, voltage, and discharge time was determined from the intensity of spectral lines. The source voltage was varied from 1 kV to 1.5 kV, and the pressure was maintained between 0.1-1 torr. As a time-dependent function, the electron temperature was calculated every 20 seconds during a 200-second discharge. The results showed that in argon plasma, as the pressure increases, the electron temperature decreases up to a pressure value of 0.4 torr, subsequent increase leads to an increase in temperature. Also, with the increase in source voltage, a decrease in electron temperature within the error limits is observed. In addition, in dust plasma (PECVD in Ar-C2H2), the electron temperature as a function of pressure and source voltage showed a trend similar to that observed in argon plasma. However, the electron temperature in dust plasma increases as a function of time at the initial moment, after which it decreases sharply with time.